A 64-Year-Old Woman with Chest Pain, Limb Weakness, and Endometrial Cancer - Simon Ponthus; Omar Kherad; Nicole Petriccioli; Johannes Alexander Lobrinus; Pierre-André A. Guerne (Case Reports in Rheumatology)
Necrotizing autoimmune myopathy (NAM) is a rare subgroup of idiopathic inflammatory myopathies (IIM). This pathology usually affects proximal limb muscles and in some cases the myocardium. Patients usually display proximal limb weakness. Muscular biopsy is required to confirm the diagnosis. We report the case of a 64-year-old woman with an atypical first presentation of NAM, manifested by chest pain in the context of metastatic endometrial cancer. The diagnosis of NAM was however made when she returned a second time with proximal limb weakness. A treatment with prednisone was then initiated, to which rituximab was rapidly associated, beside a specific chemotherapy.